Trigger Finger (Stenosing Flexor Tenosynovitis): from Definition to Conservative and Surgical Treatment Options – A Literature Review - Maulidiva, Syarifah Zahwa; Aryasta, Ida Bagus Putra Bayu; Praditna, Lalu Muhammad Ardi; Rahman, Hadian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Trigger finger, also known as stenosing flexor tenosynovitis, is a common hand disorder that impairs daily function due to painful locking and restricted motion of the affected digit. This study aimed to review and synthesize recent evidence on the definition, epidemiology, etiology and risk factors, pathophysiology, diagnostic approach, differential diagnosis, complication, and management of trigger finger in order to identify the most effective treatment strategies. A narrative literature review was conducted by searching PubMed, ScienceDirect, and Google Scholar for articles published within the last 10 years, focusing on both conservative and surgical interventions. The findings indicate that trigger finger is more prevalent in women and patients with diabetes, with corticosteroid injections and splinting showing variable but significant short‑term improvement, while surgical release particularly open A1 pulley release demonstrates consistently high long‑term success rates. In conclusion, trigger finger remains a prevalent condition with substantial functional impact, and treatment should be individualized based on patient comorbidities and severity of symptoms. It is recommended that clinicians adopt a stepwise approach, beginning with conservative management and progressing to minimally invasive surgical release when necessary. Recent futures have shown that ultrasound guidance in corticosteroid injection techniques as well as in percutaneous release offers promising results with minimal complications.